An Error Analysis of Using Plural Nouns in English Sentences” A Case Study of the Second Year Students of MA Al-Manar Tengaran in the Academic Year 2003/2004 - Mustaidah Mustaidah (Register Journal, 2009)
By doing this research, the writer hopes that the results will be helpful to the English learner in order to be more careful in using plural nouns in English sentences. The subject of research is the second year students of MA Al- Manar Tengaran in the academic year 2003/2004.The writer uses random sampling by lottery method to get the sample of research. The writer analyses the data by making the observation of all collected data, Categorizing the data by giving codes for cash data, categorizing the data by giving codes for cash data, and interpreting data info substantive theory. The result of the study shows that there are dominant errors which are made by students of second years of MA Al- Manar to use plural nouns in English.Keywords: Plural;   Random Sampling; Categorizing;  Dominant;   Error